WOMAN, MOTHER AND CITIZEN: PERONISM AND ANTIPERONISM IN THE RECOVERY OF THE FEMININE RIGHTS - Perrig, Sara (Revista de Historia Social y de las Mentalidades, 2024)
The intention of this work is to operate deconstructivamente on the feminine imaginary of the Peronism in order to show how the supposed innovation of this one about the recovery of the women rigths, especially the right to vote, it is brought down in a paradoxical speech where the ‘woman’ is over-determined for the being ‘mother’, or maternal subject. This paradojal situation, the need to agree and reject simultaneously the sexual difference, shows an unsoluble tension that is re-meant historically and of which the Peronism cannot escape. Though the antiperonist women place more than once her dispute with the latter peronism in terms of the way as Eva Perón conceptualizes the woman, it is possible to warn that they also have Only paradoxes to offer.